(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2019)
INTRODUCTION: Stiffness evaluation of healthy muscles is important to access the values of normality. Additionally, it becomes useful for choosing treatment protocols and to follow-up the injury stages. OBJECTIVES: to characterize the strain of the rectus femoris (RF), vastus lateralis (VL), and vastus medialis (VM) muscles, bilaterally, by quasi-static elastography, and to compare the strain values between limbs. MATERIALS AND METHODS: Nine subjects (males, n = 7), right-handed, participated in the study (25.9 ± 4.0 years old), approved by the local ethics and research committee on humans (2.620.204). An ultrasound coupled to a 6-15 MHz linear transducer was used to generate the elastography images of RF, VL, and VM muscles at rest. Approximately 10 compression cycles were applied using moderate pressure. Elastographic images were displayed by a color map which scale ranged from red (higher strain) to blue (lower strain). The strain ratio was obtained by strain muscle / strain adipose tissue. Two-way ANOVA (side vs. muscle) and post hoc test were used to distinguish possible significant differences (? = 0.05). RESULTS AND DISCUSSION: there was no significant interaction between the factors (p > 0.05), only for the muscle factor (p ? 0.05). This result excludes the greater loading in the dominant limb (laterality influence). VL muscle had higher values of strain ratio (lower strain) than VM (left: 4.04 ± 0.94 vs 2.71 ± 0.96 and right: 4.17 ± 0.80 vs 2.27 ± 0.62, p ? 0.05). CONCLUSION: Quadriceps muscles present similar strain between the sides at rest, however the VM deforms more than the VL.